Review on relationship between the universality class of the Kardar-Parisi-Zhang equation and the ballistic deposition model - Sayfidinov, Okhunjon; Bognar, Gabriella (Zielona Góra: Uniwersytet Zielonogórski)
We have analysed the research findings on the universality class and discussed the connection between the Kardar-Parisi-Zhang (KPZ) universality class and the ballistic deposition model in microscopic rules.
Keywords: universality class; ballistic deposition model; KPZ equation; finite-size scaling; perturbation method